Clinical and cardiovascular magnetic resonance predictors of early and long-term clinical outcome in acute myocarditis. (3rd October 2022) - Bohbot, Y; Garot, J; Hovasse, T; Unterseeh, T; Di Lena, C; Boukefoussa, W; Tawa, C; Renard, C; Limouzineau, I; Duhamel, S; Garot, P; Tribouilloy, C; et al.
Abstract: Background/Introduction: The natural history of acute myocarditis (AM) remains partially unknown and predictors of outcome are debated. Purpose: We sought to assess the impact of various cardiac magnetic resonance (CMR) parameters on early and long-term prognosis in a population of patients with AM. Methods: In a two-centre longitudinal study, we included consecutive patients with diagnosis of AM based on CMR and without haemodynamic compromise. The primary endpoint was the occurrence of an event in the acute phase (≤15 days). Secondary endpoints were the occurrence of major adverse cardiac events (MACE) and recurrence of AM during follow-up. Results: Three hundred and eighty-eight patients were included (mean age 38.5 years, 77.3% male, mean ejection fraction [EF]:56%) of which 82% (317) presented with chest pain. CMR was performed 4±2 days after index presentation. Overall, 38 patients (9.8%) had an event at the acute phase, 41 (10.6%) presented at least one MACE during follow-up (median 7.5 years, 6.6–8.9) and 30 (7.7%) experienced a recurrence of AM. By multivariate analysis, the independent predictors of initial complications were absence of chest pain (OR [95% CI] = 0.35 [0.15–0.82]), presence of syncope/pre-syncope (OR [95% CI] = 3.56 [1.26–10.02]), lower EF (OR [95% CI] = 0.94 [0.91–0.98] per %), myocardial extent of late gadolinium enhancement (LGE) (OR [95% CI] = 1.05 [1.002–1.100] per %) and absence of edema (OR [95% CI] = 0.44 [0.19–0.97]). Only age (HR [95% CI] = 1.021 [1.001–1.041] per year) and an initial alteration of EF (HR [95% CI] = 0.94 [0.91–0.97] per %) were associated with MACE during follow-up. Factors independently associated with AM recurrence were myocarditis prior to the index episodes (HR [95% CI] = 5.74 [1.72–19.22]) and viral syndrome at the index episode (HR [95% CI] = 4.21 [1.91–9.28]). Conclusion: In routine consecutive hemodynamically stable patients with diagnosis of AM based on CMR, absence of edema, reduced EF, and extent of LGE were associated with early adverse outcome. Only age and EF were associated with long-term events. Funding Acknowledgement: Type of funding sources: None.